El alma de Mesoamérica: unidad y diversidad en las concepciones anímicas - Roberto Martínez González (Journal de la Société des Américanistes)
The Mesoamerica’s soul: unity and diversity of soul conceptions. In order to illustrate the unity and diversity of the Mesoamerican world-view, we will compare different native conceptions of the soul. From this procedure we will recognize those elements that tend to keep constant across space and culture, identifying four types of soul: heart, breath, shadow and heat. Once described, we will explain, hypothetically, the manner in which these elements articulate under in the mythic scheme of the Fifth Sun.